Adductor-Related Athletic Groin Pain: A Clinical Commentary - Derrick Larkins; Robert Rowland; Michael Zarro; Odessa Addison (International Journal of Sports Physical Therapy, 2026)
Adductor-related athletic groin pain (ARAGP) is a common condition in athletes participating in multidirectional, high-intensity sports. It is challenging to diagnose and manage due to complex regional anatomy and overlapping clinical presentations. ARAGP represents the most frequently reported subtype of athletic groin pain and contributes substantially to time loss from play and performance limitation. This clinical commentary synthesizes current evidence related to the anatomy, risk factors, pathomechanics, imaging considerations, prevention strategies, rehabilitation principles, and return-to-sport decision-making in athletes with ARAGP. Established risk factors include prior groin injury, reduced eccentric hip adduction strength, hip adduction-to-abduction strength imbalances, and reduced hip range of motion. Diagnostic imaging, including magnetic resonance imaging and ultrasound, plays an important role in confirming injury location and severity when clinical findings are equivocal. Current evidence supports progressive strengthening, eccentric loading, neuromuscular training, and structured prevention programs in reducing injury incidence and facilitating safe return to participation. While movement assessment and strength profiling may aid clinical decision-making, further research is needed to clarify injury mechanisms and optimize screening and prevention strategies. The purpose of this clinical commentary is to provide clinicians and sports performance professionals with an evidence informed framework for the recognition, management, and risk reduction of adductor related athletic groin pain (ARAGP). Level of Evidence 5